Metabolomics of mothers of children with autism, idiopathic developmental delay, and Down syndrome - Mariana Parenti; Shannon Shoff; Jennie Sotelo-Orozco; Irva Hertz-Picciotto; Carolyn M. Slupsky (Scientific Reports)
Abstract Developmental delays have been associated with metabolic disturbances in children. Previous research in the childhood autism risk from genetics and the environment (CHARGE) case–control study identified neurodevelopment-related plasma metabolites in children, suggesting disturbances in the energy-related tricarboxylic acid (TCA) cycle and 1-carbon metabolism (1CM). Here, we investigated associations between children’s neurodevelopmental outcomes and their mothers’ plasma metabolite profiles in a subset of mother–child dyads from CHARGE, including those with autism spectrum disorder (ASD, n = 209), Down syndrome (DS, n = 76), idiopathic developmental delay (iDD, n = 64), and typically developed (TD, n = 185) controls. Multiple linear regression revealed associations between child neurodevelopmental outcomes and maternal plasma metabolites related to the TCA cycle, 1CM, and lipid metabolism. Despite profound metabolic disturbances in children with DS reported previously, few of these differences were observed in the mothers, which might reflect differences in gene dosage between children with DS and their euploid mothers. Notably differences in maternal metabolism related to ASD and iDD followed similar patterns of disturbance in previously reported metabolic signatures in children but were generally smaller in magnitude. Similar patterns of metabolic disturbances observed in mothers and their children with ASD or iDD could reflect shared genetic, mitochondrial, and/or environmental risk factors.